0
$\begingroup$

Is this a proper proof?

Since the integrand exhibits a singularity at $x=\pm1$, and $x=1$ belongs to our domain of integration, we need to separate the integral into two summands:

$$\int_{1}^{\infty} \frac{1}{x^3\sqrt{x^2 -1}} dx = \int_{1}^{2}\frac{1}{x^3\sqrt{x^2 -1}} dx + \int_{2}^{\infty} \frac{1}{x^3\sqrt{x^2 -1}} dx $$

The first one converges:

$$\int_{1}^{2} \frac{1}{x^3(x+1)^{1/2}(x-1)^{1/2}} dx \stackrel{u=x-1}{=} \int_{0}^1 \frac{1}{(u+1)^{3} (u+2)^{1/2} u^{1/2}} dx$$

Given that $\int_0^1 \frac{1}{x^{1/2}} dx$ converges, applying the Limit Criterion...

$$\lim_{u\to 0^+} \frac{\frac{1}{(u+1)^{3} (u+2)^{1/2} u^{1/2}}}{\frac{1}{u^{1/2}}} = \lim_{u\to 0^+} \frac{1}{(u+1)^3(u+2)^{1/2}} = \frac{\sqrt{2}}{2} \neq 0$$

...we find that our first integral also converges.

The second one converges:

For $x \in [2,+\infty)$ we have that

$$\frac{1}{x^3 (x^2-1)^{1/2}} \leq \frac{1}{x^3}$$

But $\int_2^{\infty} \frac{1}{x^3} dx$ converges. The Comparison Criterion therefore guarantees that our second integral also converges.

In conclusion, the improper integral converges.

$\endgroup$
3
$\begingroup$

Another input and hope it might be helpful:

Let $x = \sec(\theta)$ then $dx = \tan\theta \sec\theta d\theta$. With this substitution, we have that $$ \sqrt{x^2-1} = \sqrt{\tan^2 \theta} $$ and when $x = 0 \rightarrow \theta = \sec^{-1}(1) = 0$, and when $ x \to \infty \rightarrow \theta = \lim_{t \to \infty}\sec^{-1}(t) = \frac{\pi}{2}$.

Therefore, $$ \int_1^{\infty} \frac{1}{x^3\sqrt{x^2-1}} dx = \int_0^{\pi/2} \frac{\sin \theta \cos \theta}{\tan\theta } d\theta = \frac{1}{2} \int_0^{\pi/2} \frac{sin2\theta}{\tan \theta} d\theta \\ = \frac{1}{2} \int_0^{\pi/2} 2\cos^2(\theta) d\theta = \int_0^{\pi/2} \frac{cos 2\theta + 1}{2} d\theta = \frac{\pi}{4}$$

Thus, the improper integral converges.

$\endgroup$
0
$\begingroup$

There is no real problem around $x=1$.

Using Taylor expansion $$\frac{1}{x^3\sqrt{x^2 -1}}=\frac{1}{\sqrt{2} \sqrt{x-1}}-\frac{13 \sqrt{x-1}}{4 \sqrt{2}}+O\left((x-1)^{3/2}\right)$$ $$\int\frac{dx}{x^3\sqrt{x^2 -1}}=\sqrt{2} \sqrt{x-1}-\frac{13 (x-1)^{3/2}}{6 \sqrt{2}}+O\left((x-1)^{5/2}\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.